Pencemaran air raksa (Hg) sebagai dampak pengolahan bijih emas di Sungai Ciliunggunung, Waluran, Kabupaten Sukabumi - Widodo Widodo (Indonesian Journal on Geoscience, 2008)
http://dx.doi.org/10.17014/ijog.vol3no3.20083Gold ore mining at Waluran Subregency, Sukabumi Regency was carried out by an underground mining method, and only rock that contains high enough gold ore would be taken (selective mining). The gold ore from the mining was processed with a direct amalgamation method, so it produced low gold concentrate, but the concentrate of mercury discarded to the river was high enough. Monitoring result of water and sedimentation in Ciliunggunung River in 2004, showed that the river was contamined by mercury (Hg), and the contamination was above the value limit. This happened especially in August 2005 where the Hg content was about 0.218 mg/l on the Ciliunggunung River in CLG.07. The chemical analysis result of heavy metals for the water of the Ciliunggunung River in CLG.07 was known to contain Fe above the standard drinking water criteria, meanwhile Mn, Cu, Pb, and As were still under the maximum drinking water criteria value. To decrease the mercury contamination, it is suggested the process of gold ore from the amalgamation direct method to be changed to the amalgamation indirect method. The indirect gold ore amalgamation process consists of: removing fine particles by washing, grinding ore, and the amalgamation phase. The total impact of the indirect amalgamation method will increase the tying of gold by mercury, so the losing of mercury will be decreased and the gain of gold will be optimum.